Severe cellulitis from methicillin-resistant Staphylococcus aureus (MRSA) in a couple of preterm twins: a case report - Noemi Zampatti; Irene Bonato; Andrea Calandrino; Carolina Saffioti; Alessandro Parodi; Giorgia Brigati; Diego Minghetti; Luca Antonio Ramenghi (BMC, 2024)
Abstract Background Preterms are at risk of systemic infections as the barrier function of their immature skin is insufficient. The long period of hospitalization and the huge number of invasive procedures represent a risk factor for complications. Among the nosocomial infections of the skin, methicillin-resistant Staphylococcus aureus (MRSA) is associated with significant morbidity and mortality. We report a clinical case of cellulitis and abscess in two preterm twins caused by MRSA in a tertiary level Neonatal Intensive Care Unit (NICU). Case presentation Two preterm female babies developed cellulitis from MRSA within the first month of extrauterine life. The first one (BW 990 g) showed signs of clinical instability 4 days before the detection of a hyperaemic and painful mass on the thorax. The second one (BW 1240 g) showed signs of clinical instability contextually to the detection of an erythematous, oedematous and painful area in the right submandibular space. In both cases the diagnosis of cellulitis was confirmed by ultrasound. A broad spectrum, multidrug antimicrobial therapy was administered till complete resolution. Conclusions Due to the characteristic antibiotic resistance of MRSA and the potential complications of those infections in such delicate patients, basic prevention measures still represent the key to avoid the spreading of neonatal MRSA infections in NICUs, which include hand hygiene and strict precautions, as well as screening of patients for MRSA on admission and during hospital stay, routine prophylactic topical antibiotic of patients, enhanced environmental cleaning, cohorting and isolation of positive patients, barrier precautions, avoidance of ward crowding, and, in some units, surveillance, education and decolonization of healthcare workers and visiting parents.